The Level of Knowledge is a Predictor Factor of Self-Care Compliance in Patients with Heart Failure - Istianah; Nambiar, Nisha; Mohd Said, Faridah (International Journal Scientific and Professional, 2023)
Self care is essential for achieving good outcomes among patient with heart failure and a predictor of well-being. The self-care activities that these patients must perform, including adhering to a multiple medication regimen, following dietary sodium restrictions, and self-monitoring weight, managing patient symptoms. A critical component of heart failure care, remains difficult in many case. Research Objectives This study aims to analyze relationship between level of knowledge with self-care comlpiance among patient with heart failure. Research Methods This research uses a quantitative research design with cros sectional study. The number of sample at 196 participants. This research was conducted from December 2021 to February 2022. The mean of age the participants at 56 years old. The most of participants are male and below higher school. The results of the analysis showed that there was an associated between level of knowledge with self-care comlpiance among patient with heart failure in Hasan Sadikin General Hospital, Bandung, Indonesia (p value = 0.001). Conclusion Higher levels of knowledge and better self-care compliance have been associated with improved clinical outcomes among patients with heart failure. Patients who actively engage in self-care behaviors, such as medication adherence, dietary modifications, regular physical activity, symptom monitoring, and timely healthcare seeking, are more likely to experience better symptom management, reduced hospitalizations, and improved quality of life